EXPLORING DISTRIBUTION DYNAMICS IN JIMPITAN CULTURE - Aditya Pratama (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Jimpitan is a traditional practice in Java where a pinch of rice is collected from a crowd and distributed to those in need. It is a form of social capital that can be used as an economic distribution system in society. This study tries to analyze the Jimpitan culture as a social capital that can be used as a system of economic distribution in society. It also aims to examine whether the Jimpitan system can be applied as an instrument for the distribution of Islamic economics. This analysis suggests that the distribution system does not have to depend solely on the government, but can be initiated by the community themselves. The Jimpitan culture reinforces the culture of gotong-royong, which is a social activity characteristic of Indonesians, especially in Java. It fosters a sense of togetherness and can be a valuable source in the distribution of economic resources. It can also be applied as an instrument for the distribution of Islamic economics, such as Zakat, Infaq, Waqf, and Sadaqah. These instruments are based on the Islamic principle of social justice and aim to alleviate socio-economic problems. The Jimpitan culture promoting the values of togetherness and mutual cooperation, which are inherent in both Javanese philosophy and Islamic teachings